Telaah Buku Guru dan Siswa Kurikulum Merdeka Belajar Tingkat SMA - Indah Irawati; Lidya Sartika (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
The Merdeka Curriculum is a new curriculum introduced by the Ministry of Education and Culture to improve the quality of education in Indonesia. This curriculum provides freedom for educational units and teachers to develop students' potential according to their interests and talents, and the material taught is also essential material. The Merdeka Curriculum will begin to be implemented in the 2023/2024 academic year for new students at the SMA/SMK level. To support the implementation of the Independent Curriculum, the Ministry of Education and Culture has compiled and published teacher guidebooks and student books for all subjects. These books can be downloaded for free via the internet. The review of books by Independent Curriculum teachers and students aims to examine the content, structure and quality of these books from various aspects, such as conformity with competency standards, relevance to students' needs, readability, understandability and the relationship between concepts. This study also provides suggestions and recommendations for improving these books to make them more effective and efficient in the learning process. It is hoped that this study can provide input for the Ministry of Education and Culture, education units, teachers and students in implementing the Independent Curriculum.